Dampak Perubahan Temperatur Lingkungan Terhadap Temperatur Puncak Las Dan Laju Pendinginan Sambungan Dissimilar Metal Menggunakan Las Mlg - Sugiarto, Sugiarto; Wahyudi, Ari; Masduki, Masduki (Jurnal Rekayasa Mesin, 2011)
The failure of dissimilar weld joint happen to train contructions because of unweld joint quality optimal.This research used MIG welding with CO2 gas shield. The welding current used was 110 Ampere with wire diameter 0.8mm, welding velocity 2 mm/s, gas rate of CO2 was 5L/mnt. Temperature measurement distance towards welding center was 5 mm and 10mm. The joint plate was low carbon steel ST37 and austenitic stainless steel SS 304 with thickness 4mm. In order to obtain the temperature, thermocouple was used complated with ADC and computer to display and graph. Enviroment temperature was variated with room temperature 100 ºC, 200 ºC and 250 ºC. The low peak temperature cause cooling rate post welding deacreased, which was shown trough the decreasing shape of cooling graph. The higher the enviroment temperature, the lower welding peak temperature. It happen to both ST37 and SUS 304. The peak temperature and cooling rate post welding of SUS 304 was lower than ST37. The distribution of peak temperature similar the incrase of enviroment temperature. The most similar and lowest peak distribution of enviroment temperature was obtained 250ºC. Keywords: Thermal cycles, cooling rate, dissimilar metal, MIG welding, enviroment temperature.